Population genetics of group B Streptococcus from maternal carriage in an ethnically diverse community in London - Jamrozy, Dorota; Gopal Rao, Guduru; Feltwell, Theresa; Lamagni, Theresa; Khanna, Priya; Efstratiou, Androulla; Parkhill, Julian; Bentley, Stephen D. (Frontiers in Microbiology, 2023)
Introduction Maternal immunization against Group B Streptococcus (GBS) has the potential to significantly reduce the burden of neonatal GBS infections. Population genetics of GBS from maternal carriage can offer key insights into vaccine target distribution. Methods In this study we characterized the population structure of GBS isolates from maternal carriage (n = 535) in an ethnically diverse community in London, using whole genome sequencing. Results The isolates clustered into nine clonal complexes (CCs) but the majority (95%) belonged to five lineages: CC1 (26%), CC19 (26%), CC23 (20%), CC17 (13%) and CC8/10 (10%). Nine serotypes were identified, the most common were serotypes III (26%), V (21%), II (19%) and Ia (19%). Other serotypes (Ib, IV, VI, VII, IX) represented less than 10% of all isolates each. Intra-lineage serotype diversity was observed in all major CCs but was highest in CC1, which revealed nine serotypes. Nearly all isolates (99%) carried at least one of the four alpha family protein genes (alpha, alp1, alp23, and rib). All isolates were susceptible to penicillin. We found 21% and 13% of isolates to be resistant to clarithromycin and clindamycin, respectively. Prevalence of macrolide-lincosamide-streptogramin B (MLSB) resistance genes was 22% and they were most common in CC19 (37%) and CC1 (28%), and isolates with serotypes V (38%) and IV (32%). We identified some associations between maternal ethnicity and GBS population structure. Serotype Ib was significantly less common among the South Asian compared to Black women (S. Asian: 3/142, Black: 15/135, p = 0.03). There was also a significantly lower proportion of CC1 isolates among the White other (24/142) in comparison to Black (43/135) and S. Asian (44/142) women (p = 0.04). We found a significantly higher proportion of CC17 isolates among the White other compared to S. Asian women (White other: 32/142, S. Asian: 10/142, p = 0.004). Conclusion Our study showed high prevalence of GBS vaccine targets among isolates from pregnant women in London. However, the observed serotype diversity in CC1 and high prevalence of MLSB resistance genes in CC19 demonstrates presence of high risk lineages, which might act as a reservoir of non-vaccine strains and antimicrobial resistance determinants.